Complexity analysis in particulate matter measurements - Luciano Telesca; Michele Lovallo (Computational Ecology and Software, 2011)
We investigated the complex temporal fluctuations of particulate matter data recorded in London area by using the Fisher-Shannon (FS) information plane. In the FS plane the PM10 and PM2.5 data are aggregated in two different clusters, characterized by different degrees of order and organization. This results could be related to different sources of the particulate matter.